NEW MEDIA TO PROMOTE JAMBI PEOPLE'S STRUGGLE MUSEUM BASED ON DIGITAL MARKETING - Eftritianto, M Rian Indra (UI Scholars Hub, 2023)
A museum is a place to record world civilization development, especially for preserving culture and history. The museum is also used for permanent exhibitions of objects that deserve public attention, such as historical, artistic, and scientific heritage. In this regard, the museum functions as a place to serve learning, educational, and fun needs. However, nowadays, the museum is only considered a place to store antiques and ancient objects. The lack of museum enthusiasts is caused by the perception that museums are not significant places to broaden insight and knowledge. Besides, there is a lack of publications and information about museums. One great way to introduce museums is through new media based on digital marketing. Digital media is ubiquitous and relevant to today's society to introduce Jambi People's Struggle Museum. New media based on digital marketing can inform the museum's activities and educative materials. Thus, more Indonesians will know about and become interested in visiting the Jambi People's Struggle Museum.